Events Tagging in Twitter Using Twitter Latent Dirichlet Allocation - A. Al-Sultany, Ghaidaa; J. Aleqabie, Hiba (International Journal of Engineering and Technology, 2018)
Twitter has become a great platform to publish and carrying news, advisements, events, topics and even daily events in our lives. Twitter Post has limitations on the length and noise. These limitations make that the post is unsuitable for topic modeling due to sparsity.Â Â In this paper, Twitter Latent Dirichlet allocation (TLDA) methodÂ for topics modeling was applied to overcome the sparsity problem of tweets modeling. Many steps were implemented for eventÂ tagging on Twitter. First: construct aÂ datasetÂ by hashtag pooling technique, and then theÂ preprocessingÂ was performed to extract the features.Â Secondly, find the suitable number of topics through Perplexity criterion, then,Â the topics are labeled by WordNet lexicon.Â Finally,Â events are tagging using Pricewise Mutual Information (PMI) criterion.Â The dataset is constructed about various topics including the American elections, Football world cup 2018, and a natural phenomenon and many others; the number of tweets is 63458. This study shows good results in training tweets dataset.Â